RESPONS PETANI TERHADAP PENGGUNAAN COMBINE HARVERSTER PADA WAKTU PANEN PADI SAWAH DI KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Indah Listiana; Kordiyana K Rangga; Purnomojati Anggoroseto; Nanik A Purwatiningsih (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
Farmers' Response to The Use of Combine Harvester Time to Harvest Wetland Rice in Pringsewu District Lampung Province. The modernization of the agricultural sector needs to be continuously improved, one of which is by implementing agricultural mechanization. The purposes of this study were to observe the response of wetland rice farmers toward the use of a combine harvester, to analyze the relationship between individual characteristics and farmer responses against the use of a combine harvester and to assess differences in rice production levels of wetland rice farmers using a combine harvester compared to conventional harvest methods (not using a combine harvester). The study was conducted in Bulurejo Village, Gadingrejo Sub-district, Pringsewu District, Lampung Province from April to June. 2019. The assessment approach was carried out using a survey method of 112 farmers consisting of users of the combine harvester and conventional farmers, each of which was 56 farmers. The collected data consists of primary data, including farmers’ characteristics (age, education, land area, farming experience, and farmer's cosmopolitan level), farmer responses, and rice production achievement (tons/ha). The collected data were analyzed descriptively qualitatively and quantitatively, enriched with Rank Spearman correlation analysis. The results of the study showed that the response of farmers to the combine harvester was quite responsive. Farmers' responses had a positive correlation with education level and cosmopolitan level, while the number of family dependents had a negative correlation. Efforts to increase farmer responses to the use of the combine harvester can be done by increasing farmer education, both formal and non-formal education; increasing farmer's emptiness by means of active extension agents inviting farmers to seek information as well as partnership with stakeholder outside their social system. Keywords: wetland rice, farmers’ responses, combine harvester, mechanization ABSTRAK Modernisasi sektor pertanian perlu terus ditingkatkan salah satunya dengan menerapkan mekanisasi pertanian. Tujuan dari kajian adalah melihat respons petani padi sawah terhadap penggunaan combine harvester, melihat hubungan karakteristik individu dengan respons petani terhadap penggunaan combine harvester, dan mengkaji perbedaan tingkat produksi padi petani padi sawah penggunaan combine harvester dibandingkan dengan cara panen konvensional (tidak menggunakan combine harvester). Kajian dilakukan di Desa Bulurejo Kecamatan Gadingrejo, Kabupaten Pringsewu Provinsi Lampung pada bulan April sd Juni 2019. Pendekatan pengkajian dilakukan menggunakan metode survei terhadap 112 orang petani yang terdiri dari pengguna combine harvester dan petani konvensional, masing-masing 56 orang petani. Data yang dikumpulkan terdiri dari data primer, meliputi: karakteristik responden (umur, pendidikan, luas lahan, pengalaman berusahatani, dan tingkat kekosmopolitan petani), respons petani, dan capaian produksi padi (ton/ha). Data yang terkumpul dianalisis secara deskriptif kualitatif dan kuantitatif dipertajam dengan analisis korelasi Rank Spearman. Hasil kajian menunjukkan bahwa respons petani terhadap combine harvester cukup responsif. Respons petani berkorelasi positif dengan tingkat pendidikan dan tingkat kekosmopolitan, dan jumlah tanggungan keluarga yang sedikit. Upaya peningkatan respons petani terhadap penggunaan combine harvester dapat dilakukan dengan meningkatkan pendidikan petani baik pendidikan formal maupun pendidikan non formal, meningkatkan kekosmopolitanan petani dengan cara penyuluh aktif mengajak petani untuk mencari informasi, dan bermitra dengan stakeholder di luar sistem sosialnya.Kata kunci: padi sawah, respon petani, combine harvester, mekanisasi